Examining the Halal Perspective of Pre-Order Transactions in Gold Buying and Selling: A Qualitative Descriptive Analysis - Rizali, Muhammad; Pajriah, Rihani (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research will discuss buying and selling, especially buying and selling gold. Gold today is not only favored as a woman's jewelry but as a means of investment. The existence of gold buying and selling transactions by pre order raises questions that develop in the community regarding the halal and haram laws. This research is a type of qualitative descriptive research, by examining various literatures and criticizing the problems that occur in the field. By sharing opinions, from the community, religious leaders and scholars that buying and selling gold by pre order is halal. Because basically dp (downpayment) is only used as a guarantee for the buyer's certainty to buy the gold. Not as a contract. Because the correct contract is when it is paid in full and the gold has been received at the price according to the day the gold is received. Gold here is categorized as jewelry according to the illatnya "gold formed in various models is categorized as jewelry so that it is said to be goods or clothing". Keywords: buying and selling gold, buying and selling gold on pre-order, buying and selling gold on forging. Abstrak Penelitian ini membahas pembelian dan penjualan, khususnya pembelian dan penjualan emas. Saat ini, emas tidak hanya diminati sebagai perhiasan wanita tetapi juga sebagai sarana investasi. Keberadaan transaksi pembelian dan penjualan emas melalui pre order menimbulkan pertanyaan yang berkembang di masyarakat mengenai hukum halal dan haram. Penelitian ini merupakan jenis penelitian deskriptif kualitatif, dengan menelaah berbagai literatur dan mengkritisi masalah-masalah yang terjadi di lapangan. Dengan berbagi pendapat dari masyarakat, pemimpin agama, dan ulama bahwa pembelian dan penjualan emas melalui pre order adalah halal, karena pada dasarnya uang muka hanya digunakan sebagai jaminan kepastian pembeli untuk membeli emas, bukan sebagai kontrak. Kontrak yang benar adalah saat pembayaran lunas dan emas telah diterima dengan harga sesuai dengan hari emas diterima. Emas di sini dikategorikan sebagai perhiasan berdasarkan illatnya "emas yang dibentuk dalam berbagai model dikategorikan sebagai perhiasan sehingga dianggap sebagai barang atau pakaian". Kata kunci: pembelian dan penjualan emas, pembelian dan penjualan emas pre-order, pembelian dan penjualan emas secara palsu.